Family, Community and Long-Term Earnings Inequality - Paul Bingley; Lorenzo Cappellari; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2016)
This paper studies the influence of family, schools and neighborhoods on life-cycle earnings inequality. We develop an earnings dynamics model linking brothers, schoolmates and teenage parish neighbors using population register data for Denmark. We exploit differences in the timing of family mobility and the partial overlap of schools and neighborhoods to separately identify sorting from community and family effects. We find that family is far more important than community in influencing earnings inequality over the life cycle. Neighborhoods and schools influence earnings only early in the working life and this influence falls rapidly and becomes negligible after age 30.
Keywords: D31; J62; 330; sibling correlations; neighborhoods; schools; life-cycle earnings; inequality